Molecular Cytogenetics Protocols and Applications - Fan, Yao-Shan.; Fan, Yao-Shan. (Methods in Molecular Biology, 2003)
With the proliferation of fluorescence in situ hybridization (FISH) techniques as a powerful diagnostic tool in many areas of medicine, the variety and complexity of tests pose bewildering choices even for long-experienced laboratory technologists and physicians. In Molecular Cytogenetics: Protocols and Applications, Yao-Shan Fan and a panel of senior scientists and pioneering researchers describe in step-by-step fashion not only the leading FISH techniques, but also those molecular technologies beyond FISH now available for diagnostic services in genetics and oncology. The methods include labeling FISH probes for DNA and RNA targets, fluorescence genotyping, CGH microarray, spectral karyotyping/multicolor FISH, and primed in situ labeling. There are also techniques for multicolor fiber FISH, multi-telomere FISH, prenatal diagnosis using maternal blood, and preimplantation diagnosis. Oncological methods include simultaneous fluorescence immunophenotyping and FISH for leukemia and lymphoma, HER2 amplification in breast cancer, and CAC/PAC for cancer cytogenetics. Each easy-to-follow protocol offers first hand advice on how to obtain the best results, to avoid pitfalls, and to troubleshoot problems. Many protocols discuss possible future applications of the technology and explain its sensitivity and limitations. Cutting-edge and highly practical, Molecular Cytogenetics: Protocols and Applications offers laboratory physicians and scientists today's most comprehensive and up-to-date collection of FISH protocols for cancer diagnosis and investigation, plus an array of the emerging molecular technologies beyond FISH.